Application of FMEA method in halal risk determination on halal poultry slaughtering operations - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Jamaludin, Mohammad Aizat (USIM Press, 2024)
Halal slaughtered chicken has become crucial in globalization and complex supply chains. The rising awareness among Muslim communities regarding the integrity of slaughtered chicken products has led to a focus on adhering to halal compliance standards and Islamic law. This study aims to qualitatively analyze the halal risk points in chicken slaughtering operations using the Failure Mode and Effect Analysis (FMEA) method to identify potential halal risks and ensure the integrity of halal chicken products. This qualitative study uses an analytical approach by examining secondary sources, including journals, articles, guidelines, and standards related to the halal slaughtering process. In this study, seven Halal Risk Points (HRP) have been identified in the entire halal slaughtering process of broilers. Based on the risk assessment results through the FMEA method, each determined HRP will be assessed based on the severity, occurrence and detection rating scale. The final result of this study found that only six HRPs have a Risk Priority Number (RPN) value that exceeds 100. Therefore, corrective action recommendations are proposed to prevent any halal non-compliance from occurring in the process involved. Overall, the FMEA framework in this study is a new approach to guaranteeing the integrity of chicken slaughter products and can positively impact the halal chicken slaughter industry players and the implementers of the halal management system.